moringa oleifera, sıçanların submandibular bezlerinde valproik asit kaynaklı lipid peroksidasyon seviyelerindeki artışı azalttı - YARAT, AYŞEN (My University, 2022)
Moringa oleifera Lam. (M. oleifera) extracts exhibit multiple nutraceutical or pharmacological functions including anti-inflammatory, anti-oxidant, anti-cancer, hepatoprotective, neuroprotective, hypoglycemic, and blood lipid-reducing functions. Valproic acid (VPA) is a broad spectrum antiepileptic drug that is effective in migraine, bipolar disorder, anxiety and other psychiatric disorders. In addition to many known clinical side effects of VPA, it causes sialadenosis and dry mouth, and it is also claimed that VPA treatment prevents the growth of salivary gland tumors. In this study, the possible protective effect of M. oleifera alcoholic extract on the submandibular gland which is one of the major salivary glands, was investigated in VPA-treated rats. Submandibular gland lipid peroxidation values were significantly increased in the VPA group compared to the control group. Lipid peroxidation values were significantly decreased with the administration of M. oleifera extract. This work was supported by the by the Marmara University Scientific Research Projects Commission (Project No:TYL-2022-10383)Keywords: Valproic acid, M. oleifera extract, submandibular gland, lipid peroxidation
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED)